Корелација између нивоа серумског TSG-14, ALBP и EGLN1 и тежине дијабетичког макуларног мажорног едема: Серумски ТСГ-14, АЛБП и ЕГЛН1 и тежина дијабетичног макуларног мажорног едема - Zhang, Fengjiao; Jiang, Meiyi; Liu, Xinyu (Journal of Medical Biochemistry, 2026)
Objective To investigate the relationships among serum TNF-stimulated gene 14 (TSG-14), Adipocyte Lipid Binding Protein (ALBP), and Egl Nine Homolog 1(EGLN1) levels and the severity of diabetic macular edema (DME).Methods A total of 314 patients with DME who were admitted to our hospital from March 2022 to March 2025 were selected (DME group). The patients were divided into mild, moderate and severe groups according to their severity. Additionally, 314 patients with simple T2DM who were admitted to our hospital during the same period were selected (T2DM group). The levels of serum TSG-14, ALBP and EGLN1 were detected via ELISA. Logistic analysis was employed to ascertain the determinants of severe DME, and receiver operating characteristic (ROC) curves were constructed to evaluate the blood levels of TSG-14, ALBP, and EGLN1 in patients with severe DME.Results There were significant differences in the duration of diabetes, fasting blood glucose, glycosylated hemoglobin, and homocysteine levels between the T2DM group and the DME group (all P < 0.05). Compared with those in the T2DM group, the levels of serum TSG-14, ALBP, and EGLN1 in the DME group were considerably larger (all P < 0.05). Serum TSG-14, ALBP, and EGLN1 levels in the moderate and severe groups were significantly higher (all P < 0.05) than those in the mild group; serum TSG-14, ALBP, and EGLN1 levels in the severe group were significantly higher (all P < 0.05) than those in the moderate group. According to logistic analysis, EGLN1, ALBP, and TSG-14 were risk factors for severe DME (all P < 0.05). When evaluating patients with severe DME, the ROC curve results showed that the AUCs of serum TSG-14, ALBP, and EGLN1 alone and in combination were 0.781, 0.805, 0.817, and 0.950, respectively. The combined evaluation's AUC was higher than the individual evaluation's (Z = 2.699, 2.714, and 2.717, all P < 0.05).Conclusion The levels of TSG-14, ALBP and EGLN1 in the serum of DME patients were dramatically raised. These three signs are related to the severity of the condition. The combination detection approach has certain clinical utility for evaluating patients with severe DME.
Keywords: Дијабетички макуларни едем; Ген 14 стимулисан ТНФ-ом (ТСГ-14); Адипоцитна протеин за везивање липида (ALBP); Егл Нине Хомолог 1 (ЕГЛН1)